سياسات إصلاح نظام البلديات في الجزائر (دراسـة تقييميـة لقانـون البلديـة 11-10) - - بالصحراوي عبدالله, - شناف حسين; - بن حمزة عادل (Universté ELOUEd-جامعة الوادي, 2022)
تعتبر الإدارة المحلية وليدة بيئتها وإنها سابقة لنشوء الدولة المعاصرة، ومع تعقيدات وظائف ومهام الدولة ظهرت الحاجة الملحة للأخذ باستراتيجيات توزيع الصلاحيات بين الحكومة المركزية والمؤسسات المحلية، من خلال اللامركزية بشقيها التفويضي والتخويلي كأداة من أدوات الإصلاح الإداري لتوصيل الخدمات وتأكيد الكفاءة والفعالية والمساءلة حيث تختلف مبررات الأخذ بنظام الحكم المحلي من دولة إلى أخرى. تهتم هذه الدراسة بتوضيح سياسات إصلاح منظومة البلدية في الجزائر، والدور الذي تلعبه، وتبيين واقع تسييرها وفقا للقوانين والتعديلات التي طرأت عليها، ويعتبر القانون البلدي 11-10 هو القانون الساري عليها حاليا.Local Administration is considered the result of their environment and it is a precedent for the emergence of the modern state, With the complexities of the functions and tasks of the state the urgent need to adopt strategies to the distribution of powers between the central government and local institutions, through decentralization, both appeared justification for the introduction of local government from the state system to another. This study aims to clarify the policy of reforming the municipal system in Algeria and the role it plays, as well as to clarify the reality of its work in accordance with the laws and the changes that have occurred, the municipal law 11-10 is the law currently applied to it.
مذكرة ماستر
Keywords: سياسات الإصلاح لنظام البلديات; Administration is considered the result of their